Biophysical properties of mutant KCNQ1 S277L channels linked to hereditary long QT syndrome with phenotypic variability - Aidery, Parwez; Kisselbach, Jana; Schweizer, Patrick Alexander; Becker, Rüdiger; Katus, Hugo; Thomas, Dierk (Biochimica et biophysica acta. Molecular basis of disease, 2011)
Hereditary long QT syndrome (LQTS) is associated with ventricular torsade de pointes tachyarrhythmias and sudden cardiac death. Mutations in a cardiac voltage-gated potassium channel, KCNQ1, induce the most frequent variant of LQTS. We identified a KCNQ1 missense mutation, KCNQ1 S277L, in a patient presenting with recurrent syncope triggered by emotional stress (QTc=528ms). This mutation is located in the conserved S5 transmembrane region of the KCNQ1 channel. Using in vitro electrophysiological testing in the Xenopus oocyte expression system, the S277L mutation was found to be non-functional and to suppress wild type currents in dominant-negative fashion in the presence and in the absence of the regulatory ß-subunit, KCNE1. In addition, expression of S277L and wild type KCNQ1 with KCNE1 resulted in a shift of the voltage-dependence of activation by −8.7mV compared to wild type IKs, indicating co-assembly of mutant and wild type subunits. The electrophysiological phenotype corresponds well with the severe clinical phenotype of the index patient. However, investigation of family members revealed three patients that exhibit asymptomatic QT interval prolongation (QTc=493-518ms). In conclusion, this study emphasizes the value of biophysical testing to provide mechanistic evidence for pathogenicity of ion channel mutations identified in LQTS patients. The inconsistent association of the KCNQ1 S277L mutation with the clinical presentation suggests that additional genetic, epigenetic, or environmental factors play a role in defining the individual clinical LQTS phenotype.
Gesehen am 28.02.2022